Simplified Single-Stage Buck-Boost Rectifier With Proportional-Integral and Cascaded Proportional-Resonant Control Method - Guler, Naki; Komurcugil, Hasan; Bayhan, Sertac; Abu-Rub, Haitham (IEEE-Inst Electrical Electronics Engineers Inc, 2024)
This article presents a simplified single-stage buck-boost rectifier as well as a proportional-integral (PI) and cascaded proportional-resonant (PR) control methods. The design of the proposed rectifier is based on a recently introduced buck-boost inverter with the elimination of low-frequency switches in the H-bridge. It is verified that the low-frequency switches are redundant, and the rectifier can operate when these switches are replaced with diodes. Elimination of four switches as well as their drivers not only simplifies the modulation scheme, but also reduces the overall cost of the proposed rectifier. Moreover, the proposed PI and cascaded PR control method ensures almost zero steady-state error in the dc-link voltage as well as in the grid current. The correct operation of the proposed rectifier together with the proposed control method during buck and boost modes are confirmed with experimental results obtained from a 500 W prototype. The steady-state and transient results are obtained to verify that the proposed rectifier has a wide ac grid voltage and dc-link voltage operation ranges.
Keywords: Buck-boost rectifier; current control; proportional-integral (PI) control method; proportional-resonant; (PR) control method; single-stage; unity power factor; voltage control